(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تُعدّ الصورة الصلة السحرية بين الذات والعالم ، الصلة التي تصل إلى حد الامتزاج ، والعين التي تتحدث عن حلم الإنسان الذي يعيش بين جنباته ، ويقلقه في الداخل ، ولعل نمط الصورة الذي انبثق باستمرار من نمط العلاقات بين الفرد والمجتمع أصبح قاعدة لدقتها وتطورها ، وهي نتاج الخيال البشري ، وقد ظهرت لأول مرة حين أحس الإنسان بانفصاله عن الطبيعة ، ثم أخذت تتطور بتطور وعيه عبر مراحل إنتاجه في ظل الشروط التاريخية والاجتماعية والنفسية ...... وقد استطاع الشاعر سليمان زريق في مجموعته الشعرية ( أبجدية الطيف ) أن يكون الشاعر الإنسان الذي أنتج صوراً جديدة وأبدعها صوراً أودع فيها حُلُمَه الحياتي في حياة فضلى يسود فيها الحق والعدل والخير . The image is considered a magical link between the self and the world, which reaches the mixing level; and the eye which talks about the dream of the man who lives between its flanks and worries in his inner self. the pattern is perhaps emerged consistently from the type of the relationships between the individual and the society, then it becomes the base for its accuracy and its evolution. It is the product of human imagination that appeared for the first time when the human senses his secession from nature and then evolved according to the development of his consciousness through the stages of his production under the historical, social and psychological conditions. The poet Suliman Zreiq has managed, through his poetry collection (alphabetic spectrum), to be the human poet who produced new images created by his life’s dream images of having a better life where there is truth, justice and goodness.